Evaluation of in vitro corrosion behavior and biocompatibility of poly[xylitol-(1,12-dodecanedioate)](PXDD)-HA coated porous iron for bone scaffolds applications - Md Yusop, Abdul Hakim; Wan Ali, Wan Fahmin Faiz; Jamaludin, Farah Hidayah; Szali Januddi, Fatihhi; Sarian, Murni Nazira; Saad, Norazalina; Wong, Tuck‐Whye; Hidayat, Arif; Nur, Hadi (John Wiley and Sons Inc, 2024)
The present study evaluates the corrosion behavior of poly[xylitol-(1,12-dodecanedioate)](PXDD)-HA coated porous iron (PXDD140/HA-Fe) and its cell-material interaction aimed for temporary bone scaffold applications. The physicochemical analyses show that the addition of 20 wt.% HA into the PXDD polymers leads to a higher crystallinity and lower surface roughness. The corrosion assessments of the PXDD140/HA-Fe evaluated by electrochemical methods and surface chemistry analysis indicate that HA decelerates Fe corrosion due to a lower hydrolysis rate following lower PXDD content and being more crystalline. The cell viability and cell death mode evaluations of the PXDD140/HA-Fe exhibit favorable biocompatibility as compared to bare Fe and PXDD-Fe scaffolds owing to HA's bioactive properties. Thus, the PXDD140/HA-Fe scaffolds possess the potential to be used as a biodegradable bone implant. © 2024 Wiley-VCH GmbH.